Indonesian Language Instructional Design in the Merdeka Curriculum: Opportunities and Challenges in Secondary Schools - Suci Raufi Alkarima; Zamratul Ain; Syahrul R; Tressyalina; Afnita (Lembaga Yasin AlSys, 2026)
The Merdeka Curriculum places flexibility, competency development, and students’ learning needs at the center of instructional planning. However, systematic research connecting Indonesian language instructional design with the opportunities and challenges of curriculum implementation in secondary schools remains limited. This study analyzed Indonesian language instructional design within the Merdeka Curriculum and identified the opportunities and challenges associated with its implementation. A descriptive qualitative approach with a library research design was employed. Data were obtained from official government policy documents and scholarly articles selected purposively according to their relevance, recency, and source credibility. The data were collected through documentation and examined using qualitative content analysis. The findings indicate that instructional design is organized through the alignment of Learning Outcomes, sequences of learning objectives, teaching modules, and assessment practices. Key opportunities include instructional flexibility, contextual and experience-based learning, project-based learning, differentiated instruction, and teacher collaboration. Conversely, implementation is constrained by variations in teacher readiness, limited facilities, the need for continuous teaching-material development, regulatory changes, and disparities in instructional capacity across schools. The study concludes that curriculum flexibility alone is insufficient to ensure effective implementation without sustained professional and institutional support. These findings clarify the organizational components and implementation conditions required to develop Indonesian language instruction that is contextual, adaptive, and responsive to students’ learning needs.